Synthesis and characterization of polyhydrazides and poly(1,3,4-oxadiazole)s containing multiple arylene ether linkages and pendent pentadecyl chains - Tawade, Bhausaheb V.; Valsange, Nitin G.; Wadgaonkar, Prakash P. (High Performance Polymers, 2017)
A new diacylhydrazide monomer, namely, 4-(4-(4-(4-(hydrazinocarbonyl)phenoxy)-2-pentadecylphenoxy)phenoxy) benzohydrazide (HPPDPB), was synthesized starting from 4-(4-hydroxyphenoxy)-3-pentadecylphenol. HPPDPB was polycondensed with terephthalic acid chloride (TPC), isophthalic acid chloride (IPC) and a mixture of TPC and IPC (50:50 mol%) to obtain polyhydrazides containing multiple arylene ether linkages in the backbone and pendent pentadecyl chains. Polyhydrazides were subsequently cyclized in the presence of phosphorus oxychloride to obtain the corresponding poly(1,3,4-oxadiazole)s. Polyhydrazides and poly(1,3,4-oxadiazole)s exhibited inherent viscosities in the range 0.65–0.72 dL g−1 and 0.54–0.62 dL g−1, respectively, which indicated the formation of reasonably high-molecular weight polymers. Polyhydrazides were soluble in polar aprotic solvents such as N,N-dimethylformamide, N,N-dimethylacetamide (DMAc), 1-methyl-2-pyrrolidinone and pyridine whereas poly(1,3,4-oxadiazole)s exhibited excellent solubility even in common organic solvents such as chloroform, dichloromethane and tetrahydrofuran. Tough, transparent and flexible films of polyhydrazides and poly(1,3,4-oxadiazole)s could be cast from DMAc and chloroform solutions, respectively. X-Ray diffraction studies revealed amorphous nature of polyhydrazides and poly(1,3,4-oxadiazole)s and the formation of layered structure was observed due to ordered packing of pentadecyl chains. The 10% decomposition temperature (T 10) values for poly(1,3,4-oxadiazole)s were in the range 425–440°C indicating their good thermal stability. Glass transition temperature (T g) values of polyhydrazides and poly(1,3,4-oxadiazole)s were in the range 175–192°C and 92–103°C, respectively. The excellent solubility characteristics and the large gap between T g (92–103°C) and T 10 (425–440°C) values give poly(1,3,4-oxadiazole)-containing pendent pentadecyl chains better opportunities for processability.